Enhanced reversible solid-state photoswitching of a cationic dithienylethene assembled with a polyoxometalate unit. Issue 38 (23rd September 2021) - Bolle, P.; Menet, C.; Puget, M.; Serier-Brault, H.; Katao, S.; Guerchais, V.; Boucher, F.; Kawai, T.; Boixel, J.; Dessapt, R.
Abstract : The coupling of a cationic dithienylethene and a polyoxometalate in the first crystallized supramolecular assembly improves the photoswitching of the organic molecule in the solid state. Abstract : The first photochromic supramolecular assembly of a dithienylethene (DTE) cation with a polyoxometalate (POM) is elaborated. The POM unit modifies the photoswitching of the DTE in the solid state, via both steric and electronic effects, resulting in an increase of its cycloreversion rate, and an almost complete re-opening process. The crystal structure after exposure to UV light reveals a remarkable photocyclization yield of almost 28%. The structural model was greatly improved by theoretical calculations, and the absorption properties were nicely modeled from electronic structure calculations.